MEDIATION AS AWAY OF CONSTRUCTING SOCIAL REALITY - Havrylyuk, Ruslana; Patsurkivskyy, Petro (KROK Business School (BSK), 2022, 2022)
The article is devoted to the study of some insufficiently studied properties of mediation in both domestic and foreign science. Its purpose is to understand mediation as a way of constructing social reality. This goal is specified through the analysis of the following specific tasks of the article: spontaneity of mediation; mediation as a form of freedom of its participants; justice of mediation. The methodology of the article corresponds to the purpose and subject of the study. As basic cognitive tools in the process of preparing the article, the authors used the paradigm of dialogicity, axiological and anthroposociocultural approaches, in particular, such components of the latter as the social ontology of P. Berger and T. Lukman and the ontology of social facts and social institutions of J. R. Searle, and the method of structural and functional analysis. The authors of the article obtained the following new scientific results: 1. Mediation as an extrajudicial way of resolving conflicts (disputes) in society has a spontaneous nature. Its necessity and nature are determined by internal factors for the parties to mediation. 2. Mediation is an effective form of freedom for both its parties and all actors in civil society, especially individuals. It is this freedom that plays the role of the eternal engine of both the development of mediation and one of the factors in the humanization of social space. 3. Mediation is fair both in its institutional nature and as a form of social practice. Its quintessence is a steady transformation of individuals from the objects of state procedure to full-fledged subjects and creators of social space. Mediation has proved to be an effective way of constructing a new social reality. The parties to mediation, solving their own private problems on a daily basis, usually on the same private basis, are constantly changing the entire social space, creating a reconciled social environment free from total antagonisms and permanent conflicts (disputes).
MEDIATION AS AWAY OF CONSTRUCTING SOCIAL REALITY. Mediation in progress. 2022. С. 57-77
Keywords: mediation; way of constructing social reality; spontaneity of mediation; fairness of mediation; mediation as freedom